Aktualizacje antropologicznych struktur wyobraźni w wierszach Bolesława Leśmiana i Mirona Białoszewskiego - Ślósarska, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
Considerations are centred on the problem of actualisation of the anthropological structures of imagination within the chosen texts by B. Leśmian and M. Białoszewski. Theoretical point of departure is a statement by G. Durand, which concerns cultural manifestation of the fundamental pattern of experience consisting of the principles of disconnection (separation), of connection (unity), and of analogy. Those principles correspond lo two fields of the isotopies of archetypes, symbols, structures and attitudes that constitute archetypal images of day and night. In the course of examination, Durand’s theoretical assumptions are introduced as analytical procedure that reveals and explicates mechanisms of creation of the represented world in the poetry of Leśmian and Białoszewski. The mechanisms m question are based above all on establishing the principle of disconnection (separation), and compensational suspending of it; establishment and suspension consist in introducing the representations of the unity and analogy principles into the structure of the represented world, according to the integral pattern of experiences. In Leśmian’s poetry, actualisation of atlthropological structures of imagination is performed above all by mediation of image and event; in poetry of Białoszewski – by mediation of linguistic morphodynamics within the scope syntactic and semantic operations that violate the rules of phrase and clause construction in Polish. In conclusion remarks one finds reflections regarding relationship between poetical and philosophical representation of anthropological structures of imagination.